Urine Analysis has a Very Broad Prospect in the Future - Zhang, Zijuan; Liu, Jingnan; Cheng, Yaxing; Chen, Jian; Zhao, Huihui; Ren, Xiaoqiao (Frontiers in Analytical Science, 2022)
Medical tests are playing an increasingly important role in the diagnosis and treatment of diseases. Urine tests, blood tests and stool tests together constitute the three major routine examination items of modern medicine and are an important part of medical tests. Urine is a body fluid normally metabolized by the human body. Compared with using blood as a test sample, using urine as a medical test sample has many advantages, such as non-invasiveness and convenient collection. This article discusses the advantages of urine test compared with blood test, the understanding and application of urine in traditional medicine, the application of urine test in social life, the current dilemma and the future urine test may play a greater role The value and advantages are discussed, aiming to increase people's attention to urine testing by explaining the advantages of urine testing, and to discover more functions of urine testing, thereby optimizing medical testing methods and reducing the pain and fear of patients. Improve inspection efficiency, reduce national and personal medical inspection expenditures, and save medical resources.